Analisis Pajak Hotel Kategori Rumah Kost Dan Pemberdayaannya Di Kota Magelang Periode 2016 – 2018 - Lucia Rita Indrawati; endang kartini panggiarti; Lorentino Togar Lau (Universitas Negeri Padang, 2020)
The objective of the research is to find out about how far the contributions of boarding house owner that is hotel tax (especially boarding house) toward the Original Area Revenue or Pendapatan Asli Daerah (PAD) in Magelang City. Boarding house tax is one of hotel tax that is can give the contributions for tax that can paid to development of government in Magelang City. This research is do to qualitative method. The qualitative method is to do the descriptive the source of Area Original Revenue from boarding house tax in 2015-2018. The researcher also want to know about the sum of user room of boarding house, and take collaboration with the BPKAD of Magelang City to get the information about Area Original Revenue specially boarding house tax in Magelang City. The analysis use data from 2015-2017. The result of the research is government didn’t give the specially attention yet toward revenue that source from boarding house tax, so the sum of Area Original Revenue that sourced from boarding house are so relative small. Besides that, information from the questionnaires, almost a lot of society didn’t want to pay the tax. So the society didn’t have yet awareness of the country society to pay the tax. Beside that the effort of government didn’t optimally yet and didn’t have synergy collaboration yet between government and boarding house owner so boarding house owner didn’t have get attention from the government.